Wavelet transforms in estimating scatterer spacing from ultrasound echoes - Tang, Xiaoyan. (2008)
In this thesis, we propose a wavelet transform based technique, which is capable of estimating the location of each scattering center, making it possible to obtain the ISS distribution. We represent liver tissue with a point scatterer model, and show, via computer simulation and clinical data, that the use of multi-scale information in the wavelet scale-space allows us to estimate the locations of regular scattering centers. We show that both the observation noise and random ultrasound returns from unresolvable tissue-microstructure can be removed successfully in the wavelet domain via the properties of Modulus Maxima Sequence of observation across different scales.